2004
DOI: 10.1098/rstb.2004.1495
|View full text |Cite
|
Sign up to set email alerts
|

Water? What's so special about it?

Abstract: What is so special about water? Why does it have the properties it has, and how might these reasons be relevant to its apparent biological importance? By exploring the structure and dynamics of water, from the isolated molecule and its interactions, through its many crystalline phases and to its so-called anomalous liquid phase, some of its apparently unusual behaviour is rationalized. The way in which it interacts with some relatively simple interfaces is also discussed. As a result of this exploration, a che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
169
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(174 citation statements)
references
References 51 publications
(57 reference statements)
4
169
0
Order By: Relevance
“…The Downloaded By quite reasonable along the isotherm T ¼ 268 K explored, as also suggested by molecular dynamics simulations of supercooled water [12]. Within the further assumption of a multiexponential time decay of the density -density correlation function inherent to the Sears model [9], the incoherent dynamic structure factor can be cast in the following form:…”
Section: Kmentioning
confidence: 99%
See 1 more Smart Citation
“…The Downloaded By quite reasonable along the isotherm T ¼ 268 K explored, as also suggested by molecular dynamics simulations of supercooled water [12]. Within the further assumption of a multiexponential time decay of the density -density correlation function inherent to the Sears model [9], the incoherent dynamic structure factor can be cast in the following form:…”
Section: Kmentioning
confidence: 99%
“…Several review articles have reported on water structure and dynamics 5,6,7,8,9,10 , but the recent advances in instrumentation for x-ray diffraction both at synchrotron and Linac Coherent Light Source (LCLS) facilities, and for neutron diffusion at reactor sources and pulsed sources facilities provide nowadays extremely accurate data on water structure 11 , and gave access to previously unexplored states 12,13 , thermodynamic conditions 12,14,3,15 , and environments 16,17,18 . In particular, the present article reviews the most recent x-ray and neutron diffraction results about the structure of liquid water and amorphous ice.…”
Section: Introductionmentioning
confidence: 99%
“…As it is well known [15], both the hindered translational and rotational modes are present in bulk water because of intermolecular hydrogen bonds (HB) that are formed by each water molecule surrounded by four other ones. Evidently, the configuration changes when water molecules cannot move freely because of confining geometry due to which it is quite natural to expect a visible modification of water's spectrum when passing from bulk to retained water.…”
Section: Retained Water Spectramentioning
confidence: 99%
“…As can be seen, water was missing and this is surprising taking into account its importance as solvent and as the medium where life occurs [69]. Although water has been studied in thousands of simulation studies since the pioneering works of Barker and Watts [70] and Rahman and Stillinger [71], the study of its phase diagram by computer simulation has not received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that by describing the calculations for water we are also describing how to do it for any other type of molecule. Problems where the determination of the fluid-solid equilibria by molecular simulation can indeed bring new light are among others, the design of model potentials for water and other molecules [69,115,116,20], the study of nucleation [117,118,119,120,121] (where the equilibrium conditions should be known in advance), the study of the fluidsolid equilibria in colloidal systems, and also the very interesting problem of protein crystallisation. Our goal here is to describe all the details to encourage the reader to implement phase diagram calculations (including at least one solid phase) either to gain new insight on appealing problems or to improve currently available potential models.…”
Section: Introductionmentioning
confidence: 99%